The Study of the Quantitative Properties of the Alloys Ga0.35 in 0.65 As / InP - T.B. AL Hamade, Hassan; N. Sabbar, Ali; Sh. Tuhaiwer, Akeel (International Journal of Psychosocial Rehabilitation, 2020)
The thermal effects on the energy gap and the effect of the width of the potential well on the quantity properties of heterostructure nano semiconductors (Ga0.35In0.65As/InP) have been studied.The energy of quantum wells in conductive and valence bands of alloy has been calculated. Then effective energies of transition electronics and associated wavelengths within those wells have been calculated. That was noted the energy gap increases due to reducing temperature to very low degrees also noted the emergence of quantum wells whenever reducing the width of the potential well to nano dimensions. The results showed that there are improvements in the physical properties of the alloy.